Is localized chemiosmosis necessary in mitochondria? Is Lee's TELP protonic capacitor hypothesis a reasonable model? - Todd P. Silverstein (Mitochondrial Communications, 2024)
Recent high-resolution pH measurements in mitochondria show ΔpH across the F1F0 ATP synthase to be quite low, 0.07–0.32. Our meta-analysis of published values of transmembrane potential (Δψ) shows it to be identical in vivo and in vitro: -159 ± 16 mV. With the low ΔpH, the thermodynamic efficiency of proton-driven ATP synthesis exceeds 100 % for average- and low-potential (−123 mV) mitochondria, and possibly also for high-potential (−180 mV) mitochondria. Efficiencies exceeding 100 % may violate the second law of thermodynamics, and suggest a need for localized chemiosmosis, i.e., the existence of a membrane surface ΔpH that exceeds the bulk phase ΔpH by at least 0.2 units in high-potential mitochondria, and by 1.1 units in low-potential mitochondria. The lack of equilibration between protons in the bulk phase and those at the membrane surface is explained by two models which we discuss and compare: the potential well/barrier model, and the TELP protonic capacitor model.